Konsep Kebahagiaan dalam Ikigai - Azkia Febi Adhaini; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the concept of happiness in Ikigai. This research uses a type of qualitative research with a descriptive-analytical method. Data collection techniques were carried out by library research. According to Ikigai, there is no specific recipe for happiness. Each typical situation in a person's life in its own way can certainly provide a foundation for happiness. Simply put according to Ikigai, accepting yourself is a way to be happy. The conclusion is that according to the Ikigai concept, a person can get happiness with their own conditions, because each condition in a person's life has its own characteristics and of course can bring the foundation of happiness. By using the 5 pillars of Ikigai, one can find his Ikigai and achieve happiness.